Pediatric Endoscopic Endonasal Approaches for Skull Base Lesions in the Very Young: Is It Safe and Effective? - Nation, Javan; Schupper, Alexander J.; Deconde, Adam; Levy, Michael (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction The fully endoscopic expanded endonasal approach (EEA) has been shown to be safe and efficacious in pediatric patients. However, in the very young patient (ages six and under), the anatomical challenge of working through a small nasal corridor is problematic. The ability to repair the skull base and use a nasoseptal flap (NSF) has also been called into question. Here, we review skull base resections using EEA in patients aged 6 years and younger.Methods A retrospective chart review was conducted on pediatric patients age 6 years and younger who underwent EEA skull base resections over a 3-year period (June 2014 through June 2017).Results Eight children aged 6 and under with seven tumor pathologies underwent an EEA for the resection of their skull base tumors, with a mean follow-up of 1.45 years. Only chordoma cases required multiple-staged resections. There are no tumor recurrences to date. A high-flow intraoperative cerebrospinal fluid (CSF) leak was encountered in three cases, and there were no postoperative CSF leaks. CSF leaks were effectively repaired with NSFs. One patient suffered from postoperative hypopituitarism, one patient experienced recurrent epistaxis secondary to turbinate destruction by the tumor, and one patient expired 8 months postresection secondary to metastatic disease.Conclusion In our case series, EEA for skull base tumors in children aged 6 and under was a safe and effective surgical approach. Skull base defects are able to be effectively addressed with typical repairs including NSFs. Larger studies are warranted to further investigate this technique in this pediatric population.
Keywords: pediatric endoscopic endonasal approach; expanded endoscopic endonasal approach; EEA; pediatric skull base surgery; surgical complications